Fierce Fusarium solani infection in diabetic foot – A double-barrel rifle - Subha Kanthiah; Sonia Subramanian; Nagalakshmi Ranjan; Poongodi Santhana Kumarasamy (Journal of Current Research in Scientific Medicine)
Diabetic foot is one of the most serious and prevalent manifestations of diabetes mellitus. In a study conducted in Eastern India, 31.7% of diabetic patients with infections in the lower limb had positive fungal cultures. In this background, we present here a case of diabetic foot infection that progressed to gangrenous necrosis due to Fusarium solani.